PENGENALAN DAN PELATIHAN PEMBUATAN JASA PENYEDIAAN BANDWIDTH DENGAN SISTEM RT/RW NET PADA MAJELIS TAKLIM HIJABERS SAKINAH JAYAPURA - Sudarmono Sudarmono; Rahman Rahman (LPPM Uncen, 2020)
Data quota has become a basic requirement for the people at this time. Data quota can be used as a business opportunity, by providing data quota through the RT/RW Net system that utilizes the availability of fast internet connections from existing providers. The target community of this service activity is members of the Majelis Taklim Hijaber Sakinah Jayapura. This activity aims to provide knowledge about the RT / RW Net system as a provider of internet quota through Wi-Fi networks and can be used as an additional opportunity for members of Jayapura's Hijaber Sakinah. The method used in this study is the lecture method and demonstration of the use of equipment used in the RT / RW Net system.Keywords: Data Quota, RT/RW Net System, Wi-Fi, Majelis Taklim Hijaber Sakinah